DELLA protein functions as a transcriptional activator through the DNA binding of the INDETERMINATE DOMAIN family proteins - Yoshida, Hideki; Hirano, Ko; Sato, Tomomi; Mitsuda, Nobutaka; Nomoto, Mika; Maeo, Kenichiro; Koketsu, Eriko; Mitani, Rie; Kawamura, Mayuko; Ishiguro, Sumie; Tada, Yasuomi; Ohme-Takagi, Masaru; et al. (Proceedings of the National Academy of Sciences - PNAS, 2014)
DELLA protein is a key negative regulator of gibberellin (GA) signaling. Although how DELLA regulates downstream gene expression remains unclear, DELLA has been proposed to function as a transcriptional activator. However, because DELLA lacks a DNA-binding domain, intermediate protein(s) mediating the DELLA/DNA interaction are believed to be necessary for activating DELLA target genes. Here, using yeast hybrid screenings, we identified five members of INDETERMINATE DOMAIN (IDD) protein family which bind physically to both DELLA and the promoter sequence of the GA-positive regulator SCARECROW-LIKE 3 (SCL3), which previously was characterized as a DELLA direct target gene. Transient assays using Arabidopsis protoplasts demonstrated that a luciferase reporter controlled by the SCL3 promoter was additively transactivated by REPRESSOR of ga1-3 (RGA) and IDDs. Phenotypic analysis of transgenic plants expressing AtIDD3 (one of the 16 IDDs in the Arabidopsis genome) fused with the plant-specific repression domain (SRDX) supported the possibility that AtIDD3 is positively involved in GA signaling. In addition, we found that SCL3 protein also interacts with IDDs, resulting in the suppression of its target gene expression. In this context, DELLA and SCL3 interact competitively with IDD proteins to regulate downstream gene expression. These results suggest that the coregulators DELLA and SCL3, using IDDs as transcriptional scaffolds for DNA binding, antagonistically regulate the expression of their downstream targets to control the GA signaling pathway.